Motivation and academic performance in learning English through gamification - Calles-Jiménez, Romel Francisco; Camacho-Oleas, María Eugenia; Báez-Báez, José Antonio; Yánez-Valle, Viviana Vanessa (Revista de Ciencias Sociales, 2025)
The objective of this article was to determine the extent to which gamification in the classroom raises the level of motivation of higher level students, thus achieving learning objectives and improving academic performance in English as a foreign language. The research was of a comparative type in which several motivation theories are reviewed and contrasted and the game is integrated as the main strategy to raise the level of participation of students as the first objective; and, subsequently, the possible impacts on performance are analyzed. The design was of a documentary nature including different recognized data sources such as Scopus, e-Book, and Web of Science, under search criteria such as temporality and thematic relevance to include or exclude documents. Among the main findings, it was found that, for a significant group of authors, the use of games in the classroom increases participation, autonomy, interactivity and provides instant feedback. Regarding academic performance, different studies record improvements in student performance, although this requires optimal planning that considers aspects of the game such as the level of difficulty, competition, and specific skill requirements such as grammar and vocabulary.